O tempo dos benefícios sociais: a experiência urbana dos Yuhupdeh em São Gabriel da Cachoeira (AM) - Barbará, Michel Paes (2021)
This dissertation is an ethnography of the experiences of cash transfer programmes, social security and employment policies, among the Yuhupdeh, indigenous people from the Upper Rio Negro. The work analyses the demand of these groups for social benefits and job exploring the links with the contexts of socio-political relations – indigenous and non-indigenous – in the region. The first chapter deals with the presence of the Yuhupdeh in the urban context: installation in camps, strategies for maintaining families during the period, relations between groups, etc. The second chapter presents a retrospective of indigenous politics throughout the historical process up to its contemporary form, characterized by the promotion of indigenous citizenship.The third chapter discusses how money and commodities circulate in the internal logic of exchange and sharing among the Yuhupdeh people from the notion of “aid”, describing the moral and affective components of exchange relations. The fourth chapter describes and analyses the impact of social benefits and jobs on the debt economy of the regional “aviamento” system. Finally, the conclusion outlines a reflection on “civilization” from the differentiation between “time of the ancients” and “current time” in the contemporary experience of the Yuhupdeh with social benefits and jobs.